The Cost-effectiveness of Celecoxib versus Non-steroidal Anti-inflammatory Drugs plus Proton-pump Inhibitors for Treating Osteoarthritis in Algeria - Nadir Hammoumraoui; Sid Ahmed Kherraf; Joaquin Mould-Quevedo; Tarek A. Ismail (Journal of Health Economics and Outcomes Research, 2013)
# Background Cyclooxygenase-2 inhibitors such as celecoxib are as effective as non-selective non-steroidal anti-inflammatory drugs (ns-NSAIDs) in the treatment of osteoarthritis (OA), have fewer gastrointestinal side effects, but are more expensive.